Role of the EGFR/Ras/Raf pathway in specification of photoreceptor cells in the Drosophila retina. - Yang, L.; Baker, N.E. (Development, 2001)
The Drosophila EGF receptor is required for differentiation of many cell types during eye development. We have used mosaic analysis with definitive null mutations to analyze the effects of complete absence of EGFR, Ras or Raf proteins during eye development. The Egfr, ras and raf genes are each found to be essential for recruitment of R1-R7 cells. In addition Egfr is autonomously required for MAP kinase activation. EGFR is not essential for R8 cell specification, either alone or redundantly with any other receptor that acts through Ras or Raf, or by activating MAP kinase. As with Egfr, loss of ras or raf perturbs the spacing and arrangement of R8 precursor cells. R8 cell spacing is not affected by loss of argos in posteriorly juxtaposed cells, which rules out a model in which EGFR acts through argos expression to position R8 specification in register between adjacent columns of ommatidia. The R8 spacing role of the EGFR was partially affected by simultaneous deletion of spitz and vein, two ligand genes, but the data suggest that EGFR activation independent of spitz and vein is also involved. The results prove that R8 photoreceptors are specified and positioned by distinct mechanisms from photoreceptors R1-R7.